Pengaruh internal audit, efektivitas pengendalian internal, dan sistem informasi akuntansi terhadap pencegahan kecurangan (Studi pada karyawan Bank BUMN di Manado) - Kountur, Claudia Marlina; Karamoy, Herman; Gamaliel, Hendrik (Manajemen Bisnis dan Keuangan Korporat, 2025)
The study will obtain empirical evidence of the effect of internal audit, the effectiveness of internal control and accounting information systems on preventing employee fraud in state-owned banks in Manado. The research hypothesis is clear: H₁: internal audit has an effect in increasing employee fraud prevention at BUMN Banks in Manado; H₂: internal control effectiveness has an effect in increasing employee fraud prevention at BUMN Banks in Manado; H₃: accounting information systems have an effect in increasing employee fraud prevention at BUMN Banks in Manado. The research is based on two theories: fraud triangle theory and attribution theory. The population of this study was employees of state-owned banks in Manado. Eighty respondents were selected for this study, including employees from the internal audit section and the bank's operational section. The analytical tool used is multiple linear regression analysis. The results of this study are clear: internal audit, the effectiveness of internal control and accounting information systems each have an effect in increasing employee fraud prevention at BUMN Banks in Manado.